1999
DOI: 10.1007/s003810050338
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid lavage in the treatment of inadvertent intrathecal vincristine injection

Abstract: Vincristine, a widely used antineoplastic agent, is extremely toxic to the central nervous system. If given intrathecally, it produces a rapidly ascending, usually fatal, neuromyeloencephalopathy. We report a case of this complication in a 7-year-old girl with acute lymphoblastic leukemia who was receiving maintenance chemotherapy. During one treatment 0.5 mg of vincristine was erroneously injected into the lumbar subarachnoid space. Cerebrospinal fluid lavage was established within 2 h and continued for 24 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Clinical studies using CEDD of paclitaxel showed a similar complication, which was attributed to leakage of paclitaxel into the subarachnoid space (29). Accidental intrathecal administration of other anti-microtubule agents has been shown to produce a wide range of complications and should be avoided (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies using CEDD of paclitaxel showed a similar complication, which was attributed to leakage of paclitaxel into the subarachnoid space (29). Accidental intrathecal administration of other anti-microtubule agents has been shown to produce a wide range of complications and should be avoided (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, cerebrospinal fluid lavage dilutes and removes the drug, thus limiting neural damage. This is well demonstrated with antineoplasic drugs and with ionic contrast medium . For example, with accidental intrathecal vincristine administration, cerebrospinal fluid drainage and early irrigation has been related to a good outcome (prolonged survival with no encephalopathy) .…”
Section: Discussionmentioning
confidence: 88%
“…The intravenous administration of vindesine may lead to side effects, such as peripheral neurologic effects, for example paresthesias, a loss of deep tendon reflexes, or paralytic ileus (1)(2)(3)(4)(5)(6)(7)(8). However, vindesine is considered to be less toxic than the other chemotherapeutic agents, especially vincristine.…”
Section: Discussionmentioning
confidence: 99%